Statin prescribing patterns in cardiovascular risk management among outpatients with type 2 diabetes: Real-world practices at a Vietnamese general hospital - Long Bui; Thu Thi Le; Nhung Hong Dao; Hoa Thi Nguyen; Thao Thi Nguyen; Van Thi Thuy Pham; Thao Thi Bich Cao; Phuong Thanh Nguyen; Phuong T. Xuan Dong (PLoS ONE, 2026)
Objective This study aimed to evaluate the current prescribing patterns of statin therapy among outpatients with type 2 diabetes at Friendship Hospital, with a focus on alignment between treatment intensity with cardiovascular risk factors. Methods A retrospective cohort study was conducted at Friendship Hospital from December 2022 to December 2023. Patient aged 40–75 years with type 2 diabetes mellitus who attended follow-up visits were included using stratified random sampling by treatment department. Clinical data were extracted from medical records to assess cardiovascular risk based on the 2023 American Diabetes Association guideline and to document statin use, intensity, treatment continuity and related factors. Multivariate logistic regression was performed to identify factors associated with whether or not patients were prescribed statins. Results Among 407 patients, 30.5% were classified as having established ASCVD, 55.6% as having high cardiovascular risk, and 99.8% of patients were eligible for indication of high intensity statin. Despite this, none received high-intensity statin. Most patients (77.4%) were prescribed moderate-intensity statins, 8.6% received low-intensity statins, and 14.0% were not prescribed any statin. A total of 58.5% of patients received uninterrupted statin prescriptions over one year, whereas 54.3% underwent changes in statin intensity during the follow-up period. Statin prescription (versus non-prescription) was significantly influenced by the treatment department, ASCVD status, and the presence of dyslipidemia (p < 0.05). Conclusion Although statin use was common, the intensity and continuity of treatment were often inconsistent with cardiovascular risks. The absence of high-intensity statin prescriptions in a population largely at very high risk may limit the potential benefits of lipid-lowering therapy. These findings highlight the need to strengthen adherence to guideline-directed statin therapy in the management of type 2 diabetes mellitus.